Assessment of Risk Factors in Patients with Chronic Hepatitis B Referred to Dr. Labbafi Nejad’s Hospital Hepatitis Clinic 2012-2014 - Sara Abolghasemi; Shahnaz Sali; Patra Kiani (Novelty in Biomedicine, 2017)
Background: With the growing trend of unhealthy behaviors in the community, the likelihood of transmission of hepatitis B virus from infected people to society is increasing. So, early detection for preventing disease progression in patients and preventing the spread to the community has an important role. The aim of this study is assessment of risk factors in patients with chronic hepatitis B referred to Labbafi nejad’s Hospital hepatitis Clinic during 2012-2014. Materials and Methods: This cross-sectional study is done on 329 hepatitis B confirmed patients that were admitted to Labbafi nejad’s Hospital hepatitis Clinic 2012-15. Information was collected by interviewing patients by researcher-made questionnaire. Variables are, all risk factors for hepatitis B, respectively. Statistical analysis was performed by SPSS version 21. Average and frequency was used for descriptive and chi-square test was used for analysis. Results: 329 persons (59% males, 41%females) with a mean age of 44/83 years. 33/7% of these individuals have been identified through routine screening. The frequency of exposure to risk factors in this study are as follows: Some groups, such as history of dentist visit (62.3%), major surgery (45.5%) and hospitalization (54.7%) had higher prevalence than other groups. There were no cases of hepatitis B in history of cosmetics and splice joint, common use of blades and razors, HCV disease in patients at the same time, Family history of HIV positive in patients and HIV disease in patients at the same time. Conclusion: It seems to be of great importance to pay more attention to certain jobs, lifestyles and cultural matters in Iran that predispose people to a number of risk factors so as to implement measures to control HBV spread. Also, given the high levels of hepatitis B infection among housewives (in this study), it seems that increased awareness and social - health education in order to avoid unprotected sexual contact with an infected partner can be highly effective. Despite existence of a long list of risk factors, different epidemiological studies with alternative methodologies accompanied by meta-analysis of risk factors in each separate area seems to be helpful in providing information about transmission.